The Yeatsian Henry More - Roberto Bondì (Studi Irlandesi)
Henry More, a Cambridge Platonist, was a significant influence on William B. Yeats, the greatest English-language poet of the 20th century. The aim of this essay is to show the presence of some Morean philosophical themes, particularly that of anima mundi, in Yeats’s work.